National University's Strategy For Preventing The Threat Of Radicalism To Support Non-Military Defence - Andy Charman Gartika; F. G Cempaka Timur; Ahmad G. Dohamid; Alsodiq Alsodiq (CV. AFDIFAL MAJU BERKAH, 2023)
The problem of the threat of the Radicalism movement in the Campus environment is a form of non-military threat that can shake the joints of community life. This research discusses the strategy and synergy of the National University in Preventing the Threat of Radicalism in Higher Education seen from three aspects namely Ways, Means and Ends as a way through existing facilities and infrastructure to ward off acts of radicalism in the campus environment that can affect the non-military defence system. This research was conducted to answer 2 research questions related to how strategies and synergies were carried out by the National University in preventing potential threats of radicalism to support the non-military defence system. The results showed that 3 aspects must be considered when the National University Campus makes efforts to prevent the threat of radicalisation among students through the Organizational Synergy, Policy Synergy and Operational Synergy approaches. All three will form an answer resulting from the research. The suggestion that needs to be done is how the campus can implement and integrate campus policies/policy strategy and student activities/operational strategy in the Student organisation/organizational strategy.